PENGARUH PEMBERIAN PUPUK ORGANIK CAIR BONGGOL PISANG TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA (Coffea canephora) PADA MEDIA GAMBUT - safitri, nita; Rosmalinda, Rosmalinda; assrorudin, assrorudin (Politeknik Negeri Ketapang, 2023)
Coffee (Coffea sp.) is a leading export commodity developed in Indonesia because it has a relatively high economic value in the world market. This study aims to determine the effect of giving banana weevil POC to the growth of robusta coffee seedlings on peat media and to determine the optimum banana weevil POC dose that affects the growth of robusta coffee seedlings on peat media. The study was carried out at the experimental garden of the Ketapang State Polytechnic, from July to September 2021. The study used a completely randomized design (RAL) consisting of 5 treatments and 5 replications, so there were 25 experimental units. Each experimental unit consists of 3 samples so that the total number is 75 samples. The treatments were B0 = POC banana weevil 0 ml L-1, B1 = POC banana hump 30 ml L-1B2 = POC banana weevil 50 ml L-1, B3 = POC banana weevil 70 ml L-1, B4 = POC banana hump 90 ml L-1. Parameters observed were plant height, stem diameter, number of leaves, root length and root dry weight. The results of analysis of variance showed that the application of POC banana weeds significantly affected the growth of plant height, stem diameter, number of leaves, root length and root dry weight. The optimum dose of POC banana hump that can increase the growth of robusta coffee seedlings in peat media is 30 ml L-1.